Analysis of Formal Structure of Routing in the Spaces of Residential Complexes Based on Space Syntax Theory (Case Study: Mehr Housing Complex, Phase 3, Pardis, Tehran) - Seyed Tajedin Mansoori; Ismaeil Zarghami (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2020)
How to navigate the premises of residential complexes is an important issue for the architectural design of such spaces. The path that creates the axis of vision and readability for human beings can be the optimal path. The purpose of this study is to investigate the formal structure of routing in the space of residential complexes based on the theory of space syntax. In this research, a structural description of human environmental behavior based on the theoretical foundations of space syntax is presented. Also, using Depthmap X 0.50 software and by extracting graph-based methods, people's perception and interpretation of routing in the residential complex area is explained. Findings show that three types of network-based circulation, curved and linear in the design of residential complexes that human behavior according to individual and collective goals and interests, can choose one of these routes to cross. Also, according to the results, routing in a linear rotation path is the easiest way to perceive space. Network routing is also the most difficult route for people to navigate due to its lower readability. Curved routing also has good readability due to its shorter spatial depth. In general, the findings in this study showed that routing has a significant relationship with the depth of space and the visual axis of people.